Trajectories and determinants of left ventricular ejection fraction after first myocardial infarction in current era of primary coronary interventions. (3rd October 2022) - Jenca, D; Melenovsky, V; Sramko, M; Kotrc, M; Zelizko, M; Mrazkova, J; Pitha, J; Adamkova, V; Kautzner, J; Wohlfahrt, P
Abstract: Background: Left ventricular ejection fraction (EF) is an independent predictor of adverse outcomes after myocardial infarction (MI). However, contemporary data from the PCI era of MI therapy on trajectories and determinants of EF are scarce. Purpose: The present study aimed to describe the epidemiology of systolic dysfunction and EF recovery among consecutive patients hospitalized for their first MI. Methods: Data from a single-centre prospectively-designed AMBITION registry of consecutive patients hospitalized for MI between years 2017 and 2021 at a large tertiary cardiology centre were utilized. Results: Out of 1593 patients in the registry, 1065 were hospitalized for MI type I and had no previous history of heart failure (HF) or coronary artery disease. Revascularisation was performed in 93.5% of patients: 901 (84.6%) underwent PCI, 89 (8.4%) CABG and 6 (0.6%) both. At discharge, EF<40% was present in 238 (22.3%), EF 40–50% in 326 (30.6%) and EF >50% in 501 (47.0%), respectively. Patients with EF<40% were more often those who suffered subacute and anterior STEMI, had higher heart rate at admission and higher maximal troponin level, and more often HF signs requiring intravenous diuretic therapy (Table 1). In the multivariate Cox analysis, EF<40%, together with age, glomerular filtration rate, glycemia level, clinical signs of HF, and atrial fibrillation were associated with increased mortality risk. Among subjects with EF<40%, the control follow-up EF determined on a median 153 days (IQR 101–407) after discharge was available in 166 patients. Among these, systolic function recovered to EF>50% in 38 (22.9%) and improved to EF 40–50% in 45 (27.1%). Improvement in systolic function to EF>40% was predicted by lower severity of coronary artery atherosclerosis (GENSINI score), by higher discharge EF, by the lower leukocyte count, the absence of atrial fibrillation during MI hospitalization and glycemia level (Table 2). Recovery of systolic function was associated with lower mortality risk (log-rank p=0.012). Conclusion: In the current era of primary coronary intervention, only 22% of patients after the first MI have EF below 40%. Of them, EF improves in 50%, and full recovery is observed in 23% of patients. Severity or coronary atherosclerosis, inflammatory response to MI, atrial fibrillation and glucose metabolism may all affect EF recovery. These observations provide novel therapeutic targets for EF recovery. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health, Czech Republic